2020
DOI: 10.1155/2020/2862701
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Key Genes and circRNA-miRNA-mRNA Regulatory Network in Gastric Cancer

Abstract: Gastric cancer (GC) is one of the most common malignancies in the world, with morbidity and mortality ranking second among all cancers. Accumulating evidences indicate that circular RNAs (circRNAs) are closely correlated with tumorigenesis. However, the mechanisms of circRNAs still remain unclear. This study is aimed at determining hub genes and circRNAs and analyzing their potential biological functions in GC. Expression profiles of mRNAs and circRNAs were downloaded from the Gene Expression Omnibus (GEO) dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 58 publications
0
24
0
1
Order By: Relevance
“…There were several literatures using the same dataset in this study ( Chen et al, 2020 ; Chi et al, 2020 ; Li Z. et al, 2020 ; Tian et al, 2020 ; Wang F. et al, 2020 ; Wu et al, 2020 ). However, most of them selected multiple genes for GC by some routine methods and did not concentrate on one gene/biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…There were several literatures using the same dataset in this study ( Chen et al, 2020 ; Chi et al, 2020 ; Li Z. et al, 2020 ; Tian et al, 2020 ; Wang F. et al, 2020 ; Wu et al, 2020 ). However, most of them selected multiple genes for GC by some routine methods and did not concentrate on one gene/biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hsa_circ_0008274 and hsa_circ_0043256 that were derived from the ceRNA network were reported to be involved in the cancer progression [37]. Bioinformatics-related analysis suggested the significance of the understanding of the potential mechanisms of circRNAs-miRNAs-target gene network [10,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al 17 performed a bioinformatics analysis which revealed that overexpression of the IL-8 gene was associated with significantly improved prognosis of GC. However, we believe this is not in conflict with our findings, as the expression of IL-8 may be affected by multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“… 15 However, the relationship between the expression of IL-8 and the prognosis of GC patients is still unclear, and some research results are contradictory. 16 , 17 Therefore, we conducted this systematic review and meta-analysis of the prognostic significance of IL-8 expression in patients with GC.…”
Section: Introductionmentioning
confidence: 99%